Equality in Isolation: Virtual Mobility, Accessibility, and Belonging - Yeoh, Pei Ann (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
This article follows the pandemic practice of The London Improvisers Orchestra between April and June 2020 from the perspective of a Malaysian musician. Virtual mobility and accessibility, isolation and belonging: traits and tropes of the COVID-19 life.